Peace Communication of The Aceh Party: Integration of Local Wisdom Based on Religious Values - Kamaruddin Hasan; Hasan Sazali; Mailin (DAWUH : Islamic Communication Journal, 2026)
This study examines the peaceful communication practiced by the Aceh Party (PA) in integrating local wisdom grounded in religious values. Beyond its political role, PA acts as a mediator in promoting peace, reconciliation, social cohesion, and democratic consolidation in Aceh. The research focuses on PA’s communication strategies, both direct and media-mediated, in the eastern coastal region of Aceh. Adopting a descriptive qualitative approach with a constructivist-interpretive phenomenological paradigm, data were collected through in-depth interviews, participant observation, focus group discussions, and literature review. The study draws on the Qur’an and Hadith as meta-theoretical foundations, supported by theories on peaceful communication, conflict transformation, human communication, deliberative democracy, local wisdom, and social cohesion. Findings reveal that PA develops a narrative of peaceful communication rooted in traditions such as peumulia jamee, musyawarah Mukim, meuseraya, peusijuek, and peumat jaroe, reflecting dialogical, inclusive, responsive, and adaptive practices based on akhlak al-karimah, ukhuwah, amar ma’ruf nahi munkar, and rahmatan lil ‘alamin. Local wisdom functions both as a conflict-resolution mechanism and a collective educational medium. Challenges such as pragmatism, symbolism, exclusivism, and patronage may distance PA from Islamic-based local wisdom. The study proposes an integrative model of peace communication, offering insights for sustainable, inclusive peace and political stability.